INTERSEKSIONALITAS CALEG PEREMPUAN DALAM PEMILIHAN ANGGOTA LEGISLATIF 2024: STUDI KASUS AMELIA ANGGRAINI DI DAPIL DPR RI JAWA TENGAH VII - Muhammad Fikhar Azqeel Kusuma; wahid Abdulrahman (Journal of Politic and Government Studies, 2026)
Although Indonesia has implemented the 30% quota policy for women's representation, the participation and electability of female legislative candidates (caleg) still face complex challenges. This research argues that these obstacles cannot be understood solely through a single-axis framework based on gender but must be analyzed through the lens of Intersectionality. The intersectional framework highlights how various identity categories— such as gender, political status (incumbent/non-incumbent), and geography (local/non-local origin)—converge to create unique experiences of subordination and multi-layered barriers for female candidates. This study aims to deeply identify and analyze the specific forms of intersectional obstacles encountered by female legislative candidates and to elaborate on the winning strategies designed to overcome these layered barriers. Employing a qualitative approach with a case study method, the research focuses on Amelia Anggraini in the DPR RI Central Java VII Electoral District, which covers Kebumen, Purbalingga, and Banjarnegara Regencies. Data were collected through in-depth interviews, observation, and analysis of campaign documents.The findings indicate that Amelia Anggraini faced specific intersectional obstacles, namely the combination of gender barriers (masculine political stereotypes), her non-incumbent status, and her non-local origin status. These barriers necessitated the formulation of a specific and unique winning strategy, which included: 1) A Communication Strategy that focused on a narrative of capacity and substantive issues rather than solely gender identity; 2) A Networking Strategy that transcended formal party structures by building horizontal, community-based alliances; and 3) a Resource Utilization Strategy focused on logistical efficiency to compensate for capital limitations compared to incumbent opponents.This research concludes that a successful winning strategy for female legislative candidates is one that consciously dismantles and transcends the multi-layered obstacles created by the intersection of various identities. Theoretically, this study reinforces the relevance of the intersectionality framework in Indonesian electoral politics, encouraging the analysis of affirmative action policies to move from mere candidacy quotas towards structural support capable of addressing layered injustice.